2013
DOI: 10.1371/journal.pone.0081333
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Regulation of Hypoxia Inducible Factor-1α (HIF-1α) by Histone Deacetylase Inhibitor in Diffuse Large B-Cell Lymphoma

Abstract: Hypoxia inducible factor (HIF) is important in cancer, as it regulates various oncogenic genes as well as genes involved in cell survival, proliferation, and migration. Elevated HIF-1 protein promotes a more aggressive tumor phenotype, and greater HIF-1 expression has been demonstrated to correlate with poorer prognosis, increased risk of metastasis and increased mortality. Recent reports suggest that HIF-1 activates autophagy, a lysosomal degradation pathway which may promote tumor cell survival. We show here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Yuan et al demonstrated that Tenovin-6, a small molecular compound which can activate p53 and inhibit the protein deacetylase activity of purified SIRT1/2/3, can inhibit cell survival of DLBCL via blocking autophagy [50]. With respect to cancer, autophagy is often associated with a pro-survival phenotype [53,54]. In our study, we found that CUL4B could promote cell growth in DLBCL.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Yuan et al demonstrated that Tenovin-6, a small molecular compound which can activate p53 and inhibit the protein deacetylase activity of purified SIRT1/2/3, can inhibit cell survival of DLBCL via blocking autophagy [50]. With respect to cancer, autophagy is often associated with a pro-survival phenotype [53,54]. In our study, we found that CUL4B could promote cell growth in DLBCL.…”
Section: Discussionsupporting
confidence: 57%
“…Extensive number of genes and proteins were confirmed to interference autophagy and further promote tumorigenesis through regulation of different mechanisms and signal pathways, including PI3K/AKT/mTOR and JNK signaling pathways [55][56][57][58]. Aberrant activation of signaling pathways led to activation of multiple downstream effectors, including those involved in growth, survival, and autophagy [20,54]. Previously studies showed that blocking of the PI3K/AKT/mTOR and JNK signaling could reduce cell survival and function of lymphocytes [59][60][61][62], potentially regarded as a therapeutic method for DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…It is stabilized under hypoxia and supports the Warburg effect [ 16 , 47 ]. In tumor cells it can be activated also under normoxic conditions (“pseudohypoxia”) [ 14 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-CXCR4 or CXCL12R (plerixafor and others), anti-CCR5 or CCL5R (maraviroc), inhibitors of survival/proliferation factors, that is, IL6, BAFF/APRIL, and others, but also inhibitors of osteoprotegerin, and a receptor for both RANKL and TNF-related apoptosis-inducing ligand/Apo2 (TRAIL) may represent new targets for cancer therapy [ 49 , 112 , 113 ]. The complex CXCL12/CXCR4 is implicated in biological mechanisms of several B-cell malignancies, particularly for CLL, MM, and lymphoma [ 112 ].…”
Section: Targeting Microenvironmentmentioning
confidence: 99%